Adolf Hitler - politischer Zauberlehrling Mussolinis - Schieder, Wolfgang 1935- (De Gruyter Oldenbourg, 2017)
"Much has been written on Hitler's rise to power. Yet the extent to which Hitler was inspired by Mussolini is often neglected. The Italian dictator was an extremely influential role model for Hitler, and Hitler continued to back Mussolini even after he rose to power and the "Duce" became dependent on his support. Hitler and Mussolini remained political friends until the very end. This book sheds new light on this unique relationship."--Provided by publisher